PENGARUH PENDAMPINGAN INKUBATOR WIRAUSAHA TERHADAP KINERJA KEUANGAN UMKM TENANT JAMBI (STUDI KASUS UMKM TENANT INKUBATOR BISNIS UNGGUL FEB UNJA) - Muhammad Azizul Hakim (Jurnal Dinamika Manajemen, 2016)
This researches aimed to clarify whether or not there is a relationship of Entrepreneurial Incubator mentoring Against Financial Performance on Micro, Small, Medium Enterprises Tenant Jambi (Case Studies Tenant on Business Incubator economic faculty of the university Jambi) and explain the dominant variables on financial performance). The sample in this study amounted to 50 people with a sampling technique is purposive sampling . In analyzing the research data using multiple linear regression analysis. The results showed simultaneous training and guidance variables significantly influence the financial performance, and in partial consultation does not have a significant influence on the financial performance, while the dominant affect financial performance is training. From these results escort team Business Incubator economic faculty of the university Jambi should create awareness among tenant to actively participate in the consultation.